نظرية الوحدة في أساليب تعليم القواعد النحوية - Ronny Mahmuddin (البصيرة: مجلة الدراسات الإسلامية, 2024)
This research aims to describe the wihdah theory (integrated theory) regarding teaching techniques for nahwu rules, namely nahwu rules, which are taught by paying attention to the teaching of four Arabic language skills and language elements in one meeting. This research also aims to present an integrated and comprehensive analysis of the teaching of the Nahwu rules. This type of research is qualitative descriptive research using library methods. The results of the research show that there are six techniques for teaching Nahwu rules based on integrated theory, namely combining the teaching of Nahwu rules, four language skills, and language elements in one meeting. These techniques are techniques for presenting the text, then understanding the text, reading jahriyah, discussing problems, drawing conclusions, and linguistic exercises.